Pengaruh Activity Daily Living (ADL ) Dan Kegiatan Rutin Lansia Di Panti Werda Terhadap Tingkat Depresi Pada Lansia Di Panti Werda Dinas Sosial Propinsi Jawa Tengah - Fiktina Vifri Ismiriyam; Wulansari Wulansari (Indonesian Journal of Nursing Research (IJNR), 2022)
ABSTRACT The routine activities of the orphanage are routine activities carried out at the nursing home in accordance with the procedures determined by the social service for the management of the nursing home in order to meet the physical and psychosocial needs of the elderly and increase the ability of Activity Daily Living (ADL) in the elderly. The elderly who live in social institutions have a higher risk of developing or experiencing depression than the elderly who live with their family. The activities of this orphanage focus on meeting individual needs from the biopsychosocial and spiritual aspects. This study aims to see whether or not there is an effect of daily activities in the nursing home on the level of depression in the elderly. The research design was a pre-experimental one group pretest-posttest. The study consisted of 28 research respondents who were taken by purposive sampling technique. Depression levels were measured by the Geriatric Depression Scale (GDS). The respondents' level of depression was mild to moderate. The values of the GDS values before and after, with p value = 0.053 (p> 0.05). The results of this study indicate that there is no significant effect of daily routine activities on the level of depression in the nursing home, but this routine activity maintains the stability of depression levels in the elderly. Panti can find additional special interventions to treat depression in the elderly. Keywords: routine daily activities, GDS, depression in the elderly